Impact of a cefepime shortage on dosing regimens and outcomes in hospitalized adults with febrile neutropenia. (March 2021) - Haiduc, Manuela; Patel, Monank; Walsh, Thomas L; Moffa, Matthew A; Bremmer, Derek N
Background: Drug shortages may negatively impact outcomes in hospitalized patients. A cefepime dosing regimen of 1 gram every 6 hours (1 g q6h) has shown to provide similar exposures above target minimum inhibitory concentrations compared to the regimen of 2 g q8h approved by the United States Food and Drug Administration (FDA) for febrile neutropenia. Our objective was to determine if the dosing regimen of 1 g q6h amidst a cefepime shortage is an appropriate alternative for the treatment of febrile neutropenia. Methods: A retrospective chart review of hospitalized patients who received cefepime for febrile neutropenia over a two-year period was performed. Patients were grouped based on cefepime dosing strategy: 2 g q8h vs. 1 g q6h. The primary objective was to compare time to defervescence after cefepime initiation. Secondary objectives included all-cause 30-day mortality, duration of antibiotic therapy, and inpatient length of stay. Results: Seventy-five patients in each arm were included. There were no differences in baseline age or severity of illness between groups. There was no difference in the primary objective as median time to defervescence was similar between the 2 g q8h and 1 g q6h groups (69.0 vs. 65.3 h: p = 0.67). Additionally, no differences were found in the secondary objectives of all-cause 30-day mortality (10.7% vs. 9.3%: p = 0.79), duration of therapy (80.8 vs. 88.0 h: p = 0.34), or length of stay (9 vs. 7 days: p = 0.50). Conclusions: Our study identified no differences in clinical outcomes with cefepime 1 g q6h compared to the traditional FDA-approved 2 g q8h regimen for the treatment of febrile neutropenia.